The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.homp.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Is metabolic dysregulation associated with antidepressant response in depressed women in climacteric treated with individualized homeopathic medicines or fluoxetine? The HOMDEP-MENOP Study

Abstract: Metabolic dysregulation was not significantly associated with response to depression treatment in depressed climacteric women treated with individualized homeopathic treatment (IHT), fluoxetine or placebo. Due to the high prevalence of metabolic disorders and its relationship with depression in the climacteric, further investigation should be focused on whether individualized prescriptions based on classical homeopathy for depressed climacteric women have an effect on metabolic parameters, and/or if treating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Sanguinarine has also been shown to block angiotensin II in a slow, nearly irreversible and non-competitive manner: thus it probably has implications in blood pressure regulation. 72 Though a high prevalence of obesity, dyslipidemia and insulin resistance in menopausal women has been demonstrated, only the two case reports, 48,54 one observational study 53 and two RCTs 51,52 in homeopathy have evaluated the lipid profile. Pre-clinical studies of homeopathic medicines have shown positive results in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Sanguinarine has also been shown to block angiotensin II in a slow, nearly irreversible and non-competitive manner: thus it probably has implications in blood pressure regulation. 72 Though a high prevalence of obesity, dyslipidemia and insulin resistance in menopausal women has been demonstrated, only the two case reports, 48,54 one observational study 53 and two RCTs 51,52 in homeopathy have evaluated the lipid profile. Pre-clinical studies of homeopathic medicines have shown positive results in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors are antidepressants used for the treatment of anxiety disorders ( 27 ). Fluoxetine, a selective 5-HT reuptake inhibitor, is the most commonly used drug to treat patients with T2DM ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to World Health Organization (WHO), depression, which has a lifetime prevalence of more than 15 %, may become the second leading cause of death worldwide after cancer [1]. Climacteric depression is a common mental disorder in women.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological changes which precede mental symptoms aggravate depression, especially in women [3]. The results of clinical studies show that the incidence of climacteric depression accounts for about 6 % of climacteric population and 78 % of climacteric syndrome, and about 80 % of menopausal women usually experience mood disorders [4]. The incidence of suicide is higher in menopausal women than in men of same age [4].…”
Section: Introductionmentioning
confidence: 99%